Managerial Perceptions of a Low Carbon Economy: A Study - Dutta, Sujit; Roy, Sujit Kumar (Prabandhan: Indian Journal of Management, 2015)
In the wake of industrialization and continued growth of the world economy, a low carbon economy has emerged as the new paradigm to sustain growth. The Indian economy is developing rapidly; sustaining industrialization in India will demand a substantial shift in the role of companies towards the low carbon path. Presently, there is a need for urgent collective action to achieve a transition to a low carbon green and more resource efficient economy. The present study focused on enormous opportunities to invest in efficient, clean technologies, and resource efficient infrastructure, which could be inspiring and beneficial for the Indian companies in securing global solutions to reduce carbon footprints. Accordingly, the study analyzed how Indian companies are responding to environmental threats as well as the opportunities that lie ahead for low carbon green developments.